Retracted: When a giant ovarian cyst poses a diagnostic dilemma - Rajesh, B. S.; Dutta, Souradeep; Rohith, Gorrepati; Vaishanavidevi, Rajarathinam (International Journal of Research in Medical Sciences, 2020)
The article " When a giant ovarian cyst poses a diagnostic dilemma" is retracted by the Editor-in-Chief, on the request of corresponding author and co-authors. The corresponding author informed that the patient described in this article, although willingly gave her consent for revealing her clinical data for publication, later withdrew her consent after knowing about the publication of clinical material during she came for a follow up visit.